2012
DOI: 10.1021/om300683c
|View full text |Cite
|
Sign up to set email alerts
|

The Complementary Competitors: Palladium and Copper in C–N Cross-Coupling Reactions

Abstract: The C−N cross-coupling chemistry intensely developed since the late 1990s has supplied synthesists with an overwhelming number of methods to effectively combine carbon and nitrogen residues. This new chemistry relies on complexes of mainly two metals, copper and palladium, used as catalysts or stoichiometric agents. The development of new methods has revealed both similarities and differences in the principles used for the design of new catalytic systems and analysis of their reactivity and selectivity. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
206
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(210 citation statements)
references
References 652 publications
2
206
0
2
Order By: Relevance
“…Classical Ullamann coupling reactions had certain limitations, reaction conditions could be revitalized by introduction of N,N/N,O/O,O ligands and inorganic bases [10]. However, these reactions could not be fully explored like BuchwaldHartwig reaction [11] due deactivation of copper catalyst. It has been reported that higher loading of metal salt or more equivalents of ligand are required to sustain it in active form.…”
Section: Introductionmentioning
confidence: 99%
“…Classical Ullamann coupling reactions had certain limitations, reaction conditions could be revitalized by introduction of N,N/N,O/O,O ligands and inorganic bases [10]. However, these reactions could not be fully explored like BuchwaldHartwig reaction [11] due deactivation of copper catalyst. It has been reported that higher loading of metal salt or more equivalents of ligand are required to sustain it in active form.…”
Section: Introductionmentioning
confidence: 99%
“…20,[22][23][24][25] Furthermore, it would be more convenient to conduct catalysis at temperatures right below the boiling point of water without the necessity for ligands, additives and inert reaction conditions. 26 Nonetheless, we want to establish a Cu 2 Onanocatalyst which combines the advantages of classical homogeneous and heterogeneous catalyses. On the one hand, Cu(I) nanocatalysts show good yields and high TONs under moderate reaction conditions; on the other hand, excellent reaction workup and low product contamination are secured.…”
Section: Introductionmentioning
confidence: 99%
“…The renaissance of iron-catalyzed cross-coupling reactions in the last decade 15 has been triggered by their unprecedented nonclassical reactivities and selectivities in comparison with conventional Pd and Ni catalysts. 6 Recent worldwide interest in practical research applications, based on the utilization of abundant earth elements and the practical advantages of iron catalysts, including low cost, low toxicity, high availability, and easy separation of metal residues, have also demanded a much greater focus on iron-catalyzed cross-coupling reactions.…”
mentioning
confidence: 99%
“…11 Recently, there has been significant progress in cross-coupling technology based on several 3d transition-metal catalysts, such as Cr, 12 Mn, 13 Co, 14 Ni, 15 Cu, 16,17 and as well as Fe catalysts. 1826 Despite this, large paramagnetic shifts and related loss of spinspin coupling information in the NMR spectra hamper the solution-phase structural studies of catalytic intermediates in the reaction mixture.…”
mentioning
confidence: 99%